ASC nanobodies to counteract the consequences of inflammasome activation. Issue 6 (16th May 2022) - Adriouch, Sahil; Pelegrin, Pablo
Abstract : Inflammasomes are multiprotein complexes that signal by oligomerizing the apoptosis speck‐like protein with caspase recruitment and activator domain (ASC) and are involved in multiple inflammatory, metabolic and degenerative diseases. Pharmacological targeting of specific inflammasomes with small molecules is leading to the development of novel drugs for most common diseases. The targeting of ASC oligomers will result in a pan‐inflammasome treatment. In their study, Bertheloot et al (2022) developed specific anti‐ASC nanobodies and showed their efficacy to disaggregate already formed ASC oligomers and to treat inflammatory diseases in animal models. This approach represents a novel biologic‐based treatment for inflammasomes‐initiated inflammatory diseases. Abstract : P. Pelegrin & A. Sahil discuss the study by Bertheloot et al (in this issue of EMBO Mol Med) that reports specific anti‐ASC nanobodies able to disaggregate ASC oligomers and treat inflammatory diseases in animal models.